THE STATE OF HEALTH AND THE ENVIRONMENT OF THE POPULATION OF THE REPUBLIC OF KARAKALPAKSTAN (World Bulletin of Education and Learning, 2025)
As a result of the analysis of the current state of the medical and geographical situation in the health of the population of the Republic of Karakalpakstan, the general multifactorial influence of natural and anthropogenic factors was revealed, and the leading modern feature of the formation of morbidity of the population of the Republic of Karakalpakstan as an ecologically crisis region was identified. In the subpopulation of the Republic of Karakalpakstan, the main regularities of the territorial distribution of nosology in most cases are an increase in the frequency of occurrence from ecologically more favorable regions (Southern zone) to less favorable ones (Northern zone).
Keywords: Republic of Karakalpakstan, health, ecologically crisis, Aral Sea, salinization process, territorial distribution of nosology in most cases.